Changes in physical activity and sedentary behavior during the first COVID-19 pandemic- restrictions in Germany: a nationwide survey : running head physical activity during the COVID-19 restrictions - Herbolsheimer, Florian; Peters, Annette; Wagner, Sarah; Willich, Stefan N.; Krist, Lilian; Pischon, Tobias; Nimptsch, Katharina; Gastell, Sylvia; Brandes, Mirko; Brandes, Berit; Schikowski, Tamara; Schmidt, Börge; et al. (BMC public health, 2024)
The COVID-19 pandemic restrictions posed challenges to maintaining healthy lifestyles and physical well-being. During the first mobility restrictions from March to mid-July 2020, the German population was advised to stay home, except for work, exercise, and essential shopping. Our objective was to comprehensively assess the impact of these restrictions on changes in physical activity and sedentary behavior to identify the most affected groups.
Gesehen am 18.09.2025